Bases of satellite technologies are in a geodesy (Journal of Geography and Environmental Management, 2019)
Planned creation of state satellite geodesic network, establishment of the state system of coordinatesand lack of information, to this direction does a necessity to pay attention to bases of satellite technologiesin a geodesy.